2023
DOI: 10.3390/pathogens12030420
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Associated with Cryptosporidium and Giardia

Abstract: Environmental factors significantly influence the transmission of intestinal protozoan diseases. Cryptosporidiosis and giardiasis are important zoonotic diseases characterized by diarrhea, and are mainly water or foodborne diseases caused by fecal-borne oocysts. The One Health approach effectively addresses environmentally influenced zoonotic diseases. However, the impact of environmental factors on the survival of Cryptosporidium/Giardia (oo)cysts or disease transmission is mostly uncharacterized. Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…For example, in areas with mild climate, the density of Cryptosporidium oocysts and the incidence of cryptosporidiosis may be positively correlated with temperature; specifically, the temperature may be the highest monthly temperature, the average temperature in the wet season, or even the average temperature in the previous 1–3 months. In other regions (such as North America), the study found that the survival rate and infectivity of oocysts in the environment were negatively correlated with temperature, because higher temperatures increased the mortality of Cryptosporidium oocysts [ 27 , 28 ]. In Australia, there is a correlation between temperature and cryptosporidiosis incidence in rural areas, but not in urban areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in areas with mild climate, the density of Cryptosporidium oocysts and the incidence of cryptosporidiosis may be positively correlated with temperature; specifically, the temperature may be the highest monthly temperature, the average temperature in the wet season, or even the average temperature in the previous 1–3 months. In other regions (such as North America), the study found that the survival rate and infectivity of oocysts in the environment were negatively correlated with temperature, because higher temperatures increased the mortality of Cryptosporidium oocysts [ 27 , 28 ]. In Australia, there is a correlation between temperature and cryptosporidiosis incidence in rural areas, but not in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather can increase the concentration of oocysts, and heavy rainfall may cause the outbreak of cryptosporidiosis. In temperate regions, precipitation may dilute the concentration of cryptosporidium oocysts through surface water flows, resulting in a negative correlation between incidence rate and rainfall [ 27 , 28 ]. Jagai et al reported that in humid tropical climates, precipitation is a key driver of seasonal cryptosporidiosis, and the incidence of cryptosporidiosis in temperate climates peaks at high temperatures [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a meta-analysis conducted by Jagai and colleagues (2009) demonstrated that while temperature was more strongly associated with cryptosporidiosis in temperate climates, precipitation was a stronger predictor in tropical climates, though notably, neither temperature nor precipitation was significantly associated with cryptosporidiosis in arid or semi-arid climates (Jagai, Castronovo et al 2009). In the case of temperature and cryptosporidiosis, more studies have reported a positive relationship between cryptosporidiosis and temperature (Hu, Tong et al 2007, Hu, Tong et al 2007, Naumova, Jagai et al 2007, Lake, Pearce et al 2008, Jagai, Castronovo et al 2009, Ajjampur, Liakath et al 2010, Hu, Mengersen et al 2010, Hu, Mengersen et al 2010, Kent, McPherson et al 2015, Ikiroma and Pollock 2021, Ma, Destouni et al 2021, Wang, Wang et al 2023) than a negative one (Britton, Hales et al 2010, Kent, McPherson et al 2015). In the case of giardiasis, the reported relationship with temperature has been less consistent (Wang, Wang et al 2023), with some studies suggesting a positive association (Naumova, Jagai et al 2007, Britton, Hales et al 2010), others reporting a negative one (Wilkes, Edge et al 2011, Li, Chase et al 2019, Masina, Shirley et al 2019), and at least one suggesting no association (Lal, Ikeda et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of temperature and cryptosporidiosis, more studies have reported a positive relationship between cryptosporidiosis and temperature (Hu, Tong et al 2007, Hu, Tong et al 2007, Naumova, Jagai et al 2007, Lake, Pearce et al 2008, Jagai, Castronovo et al 2009, Ajjampur, Liakath et al 2010, Hu, Mengersen et al 2010, Hu, Mengersen et al 2010, Kent, McPherson et al 2015, Ikiroma and Pollock 2021, Ma, Destouni et al 2021, Wang, Wang et al 2023) than a negative one (Britton, Hales et al 2010, Kent, McPherson et al 2015). In the case of giardiasis, the reported relationship with temperature has been less consistent (Wang, Wang et al 2023), with some studies suggesting a positive association (Naumova, Jagai et al 2007, Britton, Hales et al 2010), others reporting a negative one (Wilkes, Edge et al 2011, Li, Chase et al 2019, Masina, Shirley et al 2019), and at least one suggesting no association (Lal, Ikeda et al 2013). Likewise, studies assessing the relationship between precipitation and cryptosporidiosis and giardiasis have had similarly mixed results (Miller, Lewis et al 2007, Naumova, Jagai et al 2007, Keeley and Faulkner 2008, Mons, Dumètre et al 2009, Britton, Hales et al 2010, Gonzalez-Moreno, Hernandez-Aguilar et al 2013, Lal, Baker et al 2013, Daniels, Smith et al 2016, Liu, Gong et al 2020, Wang, Wang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation